Authorized Equi-join for Multiple Data Contributors in the PKC-Based Setting. (7th June 2017) - Ma, Sha
Abstract: The Database-As-a-Service (DaaS) model provides seamless mechanisms for database management and service. As a countermeasure to security treats, encryption technologies have been widely adopted in database systems. Accordingly, privacy-preserving queries on encrypted databases has become an important research topic. In this paper, we present the first solution of authorized equi-join for multiple data contributors in the PKC-based setting. With the improved ciphertext security under checkability, our underlying cryptographic construction could be used independently as a standard procedure for many other relational operations, for instance, intersection, difference, and set union. As a feature, our scheme allows flexible authorization policies for the join operation by the controlled trapdoor transitivity, which has not yet been studied thoroughly in the literature. Our proposed scheme is efficient in encryption and execution and has a reasonable ciphertext size. It can be applied as a building block for data query in the DaaS model.